Bioactive Metabolites and Biotechnological Applications of Macroalgae of the Genus Sargassum: a Review - Santos, Thalisia C. dos; Vale, Thiago M.; Cavalcanti, Diana N.; Machado, Levi P. [UNESP]; Barbarino, Elisabete; Martins, Roberto C. C.; Obando, Johana M. C. (Soc Brasileira Quimica, 2022)
The genus Sargassum belongs to the group of tropical and subtropical brown macroalgae of shallow marine meadows. Macroalgae of this genus have often been associated with negative impacts on coastal environments due to their great capacity to produce biomass and the natural cliff events, in which this material accumulates on beaches. However, these algae are an opportunity for the bioeconomy as they are sources of value-added bioactive compounds such as phlorotannins, fatty acids, sterols, terpenoids, and polysaccharides. These molecules identified in Sargassum are applicable to the pharmaceutical industry, in anti-inflammatory, antioxidant, neuroprotective, antimicrobial, antitumor, and antiviral products, among others. In addition to the vast pharmacological potential, Sargassum products are relevant raw materials in different biotechnological sectors such as food, agriculture, bioenergetics, andcosmeticsc. This knowledge still lies in the investigative phase of development and spreads across different areas of knowledge. By knowing this, this review article aims to present and discuss information covered through 52 scientific articles, which explored 25 species of Sargassum, identifying the associated bioactive metabolites and classifying the industrial and biotechnological potential of the species. The data presented here provide the opportunity for future research with an evidence-based approach to promote the use of these organisms in product development for biotechnology sectors.
Keywords: Brown algae; Phaeophyceae; biotechnological potential; Sargassum